Developing a dynamic assessment instrument to assess reasoning skills about bacteria - Mayasari Mahfudhotul Khasanah; Murni Ramli; Sri Dwiastuti (Graduate School, Universitas Negeri Yogyakarta, 2020)
This study was aimed to develop instruments to assess reasoning skills in the form of dynamic assessment as a formative assessment to improve students’ reasoning skills about bacteria. The cake format and graduated prompting method was used in this study. The instruments were based on the Fact and Proof Diagnostic Test and Structural Communication Grid (SCG) and focused on correlational reasoning and combinatorial reasoning. The instrument's development was carried out by compiling test items according to the basic competence of bacteria at the senior high school level, conducting test trials on 93 high school students, and analyzing the results of the instrument trials. Analysis of the test instrument consists of an analysis of validity, reliability, level of difficulty, distinguishing features, and effectiveness of the distractor's function. The results showed 53 items from 67 items were valid and equipped with prompts as guiding questions for each item.